Potential Limitations of E-mail and Text Messaging in Improving Adherence in Glaucoma and Ocular Hypertension. Issue 5 (June 2015) - Saeedi, Osamah J.; Luzuriaga, Christine; Ellish, Nancy; Robin, Alan
<x xml:space="preserve">Abstract</x> Purpose: To determine how receptive patients are to the use of e-mail and text message reminders for appointments and medications. Methods: We conducted a consecutive cross-sectional survey of eligible patients with glaucoma or ocular hypertension at a private glaucoma subspecialty practice with 3 locations from February 2011 to January 2012. Main outcome measures were answers to survey questions regarding how receptive patients are to e-mail and text messaging reminders for appointments and medications. Results: Of 989 patients, 404 (40.8%) patients reported that e-mail reminders would help remember appointments and 185 (18.7%) reported that they would help for medications. Among those with access to text messaging, 280 (68.9%) reported text messaging would help them remember appointments and 193 (47.5%) reported it would help with medications. Patients who reported e-mail would help them remember medications were more likely to live in an urban location [P=0.05, odds ratio (OR)=1.84], check the internet at least daily (P⩽0.001, OR=1.04), check e-mail when not at home or the office (P=0.02, OR=1.62), and know how to open attachments (P=0.03, OR=1.87). Patients who reported that text messaging would help them remember their medications were more likely to be 40 or less (P⩽0.001, OR=8.54) and African American (P<0.001, OR=2.59). Conclusions: E-mail and text messaging reminders currently may have a limited utility in improving adherence in the general glaucoma population but may be useful in younger patients with glaucoma.